2005
DOI: 10.1111/j.1365-2958.2005.04975.x
|View full text |Cite
|
Sign up to set email alerts
|

ATP‐ and NAD+‐dependent DNA ligases share an essential function in the halophilic archaeon Haloferax volcanii

Abstract: SummaryDNA ligases join the ends of DNA molecules during replication, repair and recombination. ATP-dependent ligases are found predominantly in the eukarya and archaea whereas NAD + + + + -dependent DNA ligases are found only in the eubacteria and in entomopoxviruses. Using the genetically tractable halophile Haloferax volcanii as a model system, we describe the first genetic analysis of archaeal DNA ligase function. We show that the Hfx. volcanii ATP-dependent DNA ligase family member, LigA, is non-essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 36 publications
2
49
0
Order By: Relevance
“…Phylogenetic analysis of the sequences presented here is consistent with previous studies of DNA ligases (Nakatani et al 2000). However, the addition of amino acid sequences for FaLig and related enzymes from other Thermoplasmatales identified that these are more similar to DNA ligases that have been characterized from Crenarchaeota (Jeon and Ishikawa, 2003;Kletzin 1992;Lai et al 2002) compared to those from Euryarchaeota (Gunther et al 2002;Keppetipola and Shuman 2005;Nakatani et al 2000;Rolland et al 2004;Sriskanda et al 2000;Zhao et al 2006). This phylogenetic description suggests that lateral gene transfer has occurred in the evolution of the DNA ligases of the Euryarchaeota.…”
Section: Biochemical Characterization Of Nick-joining By Faligsupporting
confidence: 89%
See 3 more Smart Citations
“…Phylogenetic analysis of the sequences presented here is consistent with previous studies of DNA ligases (Nakatani et al 2000). However, the addition of amino acid sequences for FaLig and related enzymes from other Thermoplasmatales identified that these are more similar to DNA ligases that have been characterized from Crenarchaeota (Jeon and Ishikawa, 2003;Kletzin 1992;Lai et al 2002) compared to those from Euryarchaeota (Gunther et al 2002;Keppetipola and Shuman 2005;Nakatani et al 2000;Rolland et al 2004;Sriskanda et al 2000;Zhao et al 2006). This phylogenetic description suggests that lateral gene transfer has occurred in the evolution of the DNA ligases of the Euryarchaeota.…”
Section: Biochemical Characterization Of Nick-joining By Faligsupporting
confidence: 89%
“…The majority of archaeal DNA ligases that have been experimentally analysed use ATP as the co-factor for ligation, although those from some Euryarchaeota can also use other nucleotides (Jeon and Ishikawa 2003;Nakatani et al 2000;Rolland et al 2004;Zhao et al 2006). To assess the situation with FaLig, we analysed nick-joining in the presence of a variety of cofactors (Fig.…”
Section: Biochemical Characterization Of Nick-joining By Faligmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacterial DNA ligases use NAD and the mammalian enzymes use ATP for adenylation (32). Although there are exceptions (62,71), the archaeal ligases are considered ATP dependent and exhibit sequence homology with eukaryotic enzymes (12), and some of them have also been demonstrated to utilize ADP with similar efficiency (25). This is consistent with our results, which showed that addition of NAD increased the level of repaired DNA to a level somewhat greater than the control level, while addition of ATP and ADP resulted in a Ͼ1-order-of-magnitude increase in the level of the repair product following incubation for 60 min (Fig.…”
mentioning
confidence: 99%